Public finance: fiscal policy - Cauvery, R...[et al] (New Delhi, 2003)
The text has been carefully written to incoprporate all that is relevant from the examination of the past question papers and the emerging trends. The main aim is to present the matter in such way that the students can have a clear, correct, elaborate and in-depth analysis of the subject. Table Of Contents: Nature and Scope of Public Finance | The principle of Maximum Social Advantage | The theory of Public Goods | Public Expenditure | Public Revenue | Incidence and shifting | Taxes of the centre and the states | Public Debt | Deficit Financing | financial Adminsitration | Federal Finance | local Finance | Fiscal Policy | Public Enterprises | Indian Tax Reforms | Indian Tax Reforms | Black Money
Keywords: Finance, public